THE BIOPRODUCTIVITY PROPERTY OF SINGLE-HUMPED CAMELS - A.K. Tleumuratov; А.P. Ajimuratov (Journals Park Publishing, 2022)
This article presents the biological characteristics of single-cropped camels, the products obtained from them and the conditions of Sagittarius, which are present in our Republic.
Keywords: dromedar; saksovul; cherkez